Teaching American Studies within Intellectual History (idéhistoria) - David Östlund (American Studies in Scandinavia)
This article reflects on the author’s experience of creating and teaching a set of courses with North American themes within the academic discipline of idéhistoria, intellectual history, at a Swedish university. It stresses the value of an area studies approach for training students in “a researcher’s way to see and work” within this discipline. The more courses with themes from the US (and Canada) become “American studies,” the better they contribute to prepare students to think about past thought in a way that defines the task of idéhistoria (in the author’s opinion), namely a strictly contextualist approach. The article offers some examples of this. The fact that much about the US is familiar to Swedish students creates opportunities to understand past thought historically by exploring contexts that gradually make apparently familiar things less familiar, thus allowing them to be understood in unfamiliar ways. The courses have also become exercises in linguistic and cultural translation from American English, as a language that is fairly familiar to most Swedish students becomes more complex in their perception, with meanings and bearings shifting in time and space.